2019
DOI: 10.1186/s12864-019-5572-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential isoform expression and alternative splicing in sex determination in mice

Abstract: BackgroundAlternative splicing (AS) may play an important role in gonadal sex determination (GSD) in mammals. The present study was designed to identify differentially expressed isoforms and AS modifications accompanying GSD in mice.ResultsUsing deep RNA-sequencing, we performed a transcriptional analysis of XX and XY gonads during sex determination on embryonic days 11 (E11) and 12 (E12). Analysis of differentially expressed genes (DEG) identified hundreds of genes related to GSD and early sex differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 70 publications
(86 reference statements)
2
15
0
Order By: Relevance
“…Our study confirms and complements previous findings accumulated in humans and other species (Nef et al, 2005;Beverdam and Koopman, 2006;Jameson et al, 2012b;Zhao et al, 2018;Planells et al, 2019). For instance our dataset validates the onset of SRY transcription prior to 6 PCW in the testis as early as 6 PCW (previously reported at only 6.8 PCW in (Mamsen et al, 2017)), which may reflect the higher sensitivity of RNA-seq as compared to microarrays (Mantione et al, 2014).…”
Section: Distinct Cellular Expression Patterns Of Newly Identified Genes Involved In Human Sex Determinationsupporting
confidence: 93%
“…Our study confirms and complements previous findings accumulated in humans and other species (Nef et al, 2005;Beverdam and Koopman, 2006;Jameson et al, 2012b;Zhao et al, 2018;Planells et al, 2019). For instance our dataset validates the onset of SRY transcription prior to 6 PCW in the testis as early as 6 PCW (previously reported at only 6.8 PCW in (Mamsen et al, 2017)), which may reflect the higher sensitivity of RNA-seq as compared to microarrays (Mantione et al, 2014).…”
Section: Distinct Cellular Expression Patterns Of Newly Identified Genes Involved In Human Sex Determinationsupporting
confidence: 93%
“…We also identified 27 and 16 sex-specific genes in male and female PMRs that are also highly methylated in pig blastocysts (Additional files 5 and 6). Moreover, we found 156 and 143 genes containing PMRs in male and female germ cells, respectively, that are differentially expressed in male and female embryos during sex determination or express different isoforms in a sex-specific way in mice (Additional file 8) [44]. We also found that 45 of the genes containing PMRs identified in male germ cells and 48 in female germ cells are differentially expressed during sex determination in the cow (Additional file 8) [45].…”
Section: Demethylation-resistant Genomic Elements Are Candidate Players In Sex Determination and Early Differentiationmentioning
confidence: 75%
“…Different isoforms of the same gene can regulate specific developmental and physiological processes (Graveley 2001; Baralle and Giudice 2017). Although alternative splicing has been shown to be important for sex determination in Drosophila (Burtis and Baker 1989) and for the development of sex-specific tissues in other species (Telonis-Scott et al 2009; Gibilisco et al 2016; Planells et al 2019), the overall importance of sex-specific alternative splicing remains largely underexplored (McIntyre et al 2006). This is because detecting full-length isoforms is difficult when using short read RNA-seq.…”
Section: Resultsmentioning
confidence: 99%